Estimación de la demanda energética mensual mediante encuesta aplicada en la Provincia de Santa Elena - Pavón, Christian (2015)
For the optimal sizing of a microgrid system it is very important to identify the location, the renewable energy potential and the monthly energy demand of household consumption. This paper presents the methodology and results of a survey of electric energy consumption that was applied in situ to a sample of the population of households in Atahualpa, a rural parish in the province of Santa Elena. These collected results were tabulated and processed. The average of the demand for electric energy monthly for housing was estimated by means of statistical sampling. The monthly consumption of electricity for households was 195 kWh and for business houses was 446 kWh. The monthly per capita consumption was 39 kWh. Finally, this study shows the importance of the methodology and results obtained. They can be used to make decisions in the energy field, both in terms of region and country level, through appropriate public policies to address the problem of better energy redistribution.